Incidence and risk factors for suicide, death due to substance use, and violent/accidental death in people with HIV. (1st January 2023) - Tusch, Erich S.; Ryom, Lene; Fursa, Olga; Peters, Lars; Østergaard, Lars; Florence, Eric; Edwards, Simon; Hoffmann, Christian; Sambatakou, Helen; Reiss, Peter; Shahar, Eduardo; Reikvam, Dag Henrik; et al.
Abstract : Objective: Deaths due to suicide, substance use and violence/accident may reflect similar risk factors and overlap in their classification. This study aimed to investigate incidence and risk factors of mortality among people with HIV (PWH) due to these three related causes. Design: Prospectively collected data from PWH at least 18 years old and under active follow-up in the EuroSIDA study from 2007 to 2019 were analysed. Methods: Cause-specific Cox regression analysis was used to assess risk factors. Results: A total of 17 881 participants were included, comprising 149 327 person-years of follow-up (PYFU). Forty participants died by suicide incidence rate [IR] [95% confidence interval (CI)]: 0.3/1000 PYFU (0.2, 0.4) 93 from substance use [IR (95% CI): 0.6/1000 PYFU (0.5, 0.8)], and 57 by violence/accident [IR (95% CI): 0.4/1000 PYFU (0.3, 0.5)]. An AIDS diagnosis within the last 12 months was associated with nine-fold increased risk of suicide vs. no history of AIDS [adjusted hazard ratio (aHR): 9.06; 95% CI: 2.07, 39.7]. Male gender was associated with double the risk of violent/accidental death (aHR: 2.28; 95% CI: 1.09, 4.78). PWH in Eastern Europe and those who acquired HIV by injection drug use (IDU) demonstrated a greater risk of death due to substance use or violence/accident. Conclusions: The association between a recent diagnosis of AIDS and suicide highlights a critical period for intervention. HIV infection acquired through IDU demonstrated an expected relationship with death due to substance use and violent/accidental deaths. Increased risk of death due to substance use and violence/accident in Eastern Europe demands investigation into specific differences that may drive that association.